Coconut water drink and the risk of hyperkalaemia in diabetes. (20th April 2016) - Devgun, MS
Abstract: Coconut water is available as a substitute for table water and as a sports rehydrating drink. Because of the nature of its micronutrients, it may lead to biochemical changes that may not be beneficial for all groups of people. A patient with type 2 diabetes mellitus consumed daily around one litre of coconut water drink. As a result, there was a gradual increase in serum potassium. On cessation of beverage consumption, serum potassium decreased to within the reference interval. However, an increase in urea and creatinine concentration did not revert to the level seen prior to coconut water consumption. There was a decrease in serum alkaline phosphatase and zinc when consuming the beverage. Reduction occurred in diastolic blood pressure, estimated glomerular filtration rate, serum enzymes and zinc, while serum potassium concentration increased in this patient with type 2 diabetes. The observed changes resulted from consuming excessive quantities of coconut water drinks. In patients with diabetes and renal impairment and on potassium‐retaining medication, there is a high risk of developing hyperkalaemia. Copyright © 2016 John Wiley & Sons.